Attack of the shadow smashers - Cummings, Troy (New York : Scholastic, Branches, 2013)
The latest monsters threatening Stermont Elementary are shadowy shapeshifters that attach themselves to people, eat their shadows, and block out all light--but before he can think of a way to deal with them, Alexander has to deal with a startling revelation from his friend Nikki.
Keywords: Monsters -- Juvenile fiction; Shades and shadows -- Juvenile fiction; Best friends -- Juvenile fiction; Elementary schools -- Juvenile fiction; Horror tales; Monsters -- Fiction; Shadows -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Elementary schools -- Fiction; Schools -- Fiction; Horror stories; Horror fiction